2015
DOI: 10.1007/s00464-015-4614-y
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus morphine infusion following laparoscopic bariatric surgery: effect on supplemental narcotic requirement during the first 24 h

Abstract: An intravenous infusion of dexmedetomidine, initiated and continued for 24 h following laparoscopic bariatric surgery, can decrease the overall morphine requirements during this period. This pilot study demonstrated that the post-operative initiation of dexmedetomidine can be morphine sparing following laparoscopic bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Of 10,949 citations initially identified in the search, 7,497 remained after removal of duplicates, 7,263 were excluded at title and abstract screening, and 200 at full-text review leaving 34 trials that met eligibility criteria. Of these, 11 studied dexmedetomidine ( 19 29 ), seven studied acetaminophen ( 30 36 ), six studied nonsteroidal anti-inflammatory drugs (NSAIDs) (including diclofenac, indomethacin, and ketoprofen) ( 30 , 31 , 33 , 37 – 39 ), four studied ketamine ( 40 43 ), three studied nefopam ( 37 , 44 , 45 ), two studied tramadol ( 30 , 46 ), two studied gabapentin ( 47 , 48 ), two studied carbamazepine ( 48 , 49 ), one studied clonidine ( 50 ), one studied magnesium sulfate ( 51 ), and one studied pregabalin ( 52 ). Several studies had multiple intervention arms studying more than one adjuvant analgesic in comparison to an opioid alone.…”
Section: Resultsmentioning
confidence: 99%
“…Of 10,949 citations initially identified in the search, 7,497 remained after removal of duplicates, 7,263 were excluded at title and abstract screening, and 200 at full-text review leaving 34 trials that met eligibility criteria. Of these, 11 studied dexmedetomidine ( 19 29 ), seven studied acetaminophen ( 30 36 ), six studied nonsteroidal anti-inflammatory drugs (NSAIDs) (including diclofenac, indomethacin, and ketoprofen) ( 30 , 31 , 33 , 37 – 39 ), four studied ketamine ( 40 43 ), three studied nefopam ( 37 , 44 , 45 ), two studied tramadol ( 30 , 46 ), two studied gabapentin ( 47 , 48 ), two studied carbamazepine ( 48 , 49 ), one studied clonidine ( 50 ), one studied magnesium sulfate ( 51 ), and one studied pregabalin ( 52 ). Several studies had multiple intervention arms studying more than one adjuvant analgesic in comparison to an opioid alone.…”
Section: Resultsmentioning
confidence: 99%
“…Of 10,949 citations initially identified in the search, 7,497 remained after removal of duplicates, 7,263 were excluded at title and abstract screening, and 200 at full-text review leaving 34 trials that met eligibility criteria. Of these, 11 studied dexmedetomidine (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), seven studied acetaminophen (30)(31)(32)(33)(34)(35)(36), six studied nonsteroidal anti-inflammatory drugs (NSAIDs) (including diclofenac, indomethacin, and ketoprofen) (30,31,33,(37)(38)(39), four studied ketamine (40)(41)(42)(43), three studied nefopam (37,44,45), two studied tramadol (30,46), two studied gabapentin (47,48), two studied carbamazepine (48,49), one studied clonidine (50), one studied www.ccejournal.org 3 magnesium sulfate (51), and one studied pregabalin (52). Several studies had multiple intervention arms studying more than one adjuvant analgesic in comparison to an opioid alone.…”
Section: Resultsmentioning
confidence: 99%
“…Additional trials have shown that the addition of dexmedetomidine to a sufentanil infusion achieved better analgesic effect and greater patient satisfaction in patients undergoing abdominal hysterectomy for 72 hours postoperatively [13]. Intraoperative infusions of dexmedetomidine have also shown that postoperative pain scores and Ramsay Sedation Scale scores were lower and morphine consumption was lower during the first 24 hrs after surgery [14]. When dexmedetomidine was added to propofol and remifentanil in patients undergoing an abdominal colectomy, they had lower visual analog pain scores and consumed less morphine compared to the addition of saline to propofol and remifentanil [15].…”
Section: Discussionmentioning
confidence: 99%